Bangladesh Agricultural Value Chain (AVC) Impact Evaluation: Midline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Funded under the Feed the Future (FTF) Initiative, the Bangladesh Agricultural Value Chains (AVC) project being implemented by Development Alternatives International (DAI) is working to improve food (and nutrition) security through strengthened agricultural value chains. This dataset contains data from the second round of household survey interviews from the impact evaluation of the Bangladesh AVC project. The dataset contains three respondent groups. Group 1 households are jute farmer households who were previously interviewed in 2016. Group 2 households are jute farmer households added to the sample at midline (2017). Group 3 households are local jute input retailers. The dataset contains information on: household composition and socio-demographic characteristics of household members; agricultural production (including jute, other crops, input & labor usage, and agricultural practices used; relations with other value chain actors (input sellers); and household assets and expenditures on food and non-food items.